Biochar amendment enhances water use efficiency in alfalfa (Medicago sativa L.) under partial root-zone drying irrigation by modulating abscisic acid signaling and photosynthetic performance - Zhong, Shangzhi; Zhang, Xiang; Hou, Pengxin; Ouyang, Jianghan; Rakotoson, Tovohery; Zheng, Congcong; Tao, Qibo; Sun, Juan (Elsevier, 2025)
Deficit irrigation can potentially increase plant water use efficiency by regulating stomatal morphology and photosynthetic physiology, whereas the combined effects of biochar amendment and deficit irrigation on alfalfa growth and leaf physiology remain largely unknown in salt-affected soil. A split-root pot experiment was implemented to investigate the effect of biochar amendments (WSB: wheat straw biochar; CSB: corn straw biochar) and irrigation regimes (FI: full irrigation; DI: deficit irrigation, 70 % of FI on the entire root zone; PRDI: partial root-zone drying irrigation, only irrigating half of the root zone with soil water content maintained at the same level as that under DI) on the leaf morpho-physiological traits and water use efficiency of alfalfa (Medicago sativa L.). DI and PRDI exhibited a similar trend, with both leading to a significant reduction in stomatal conductance (gs), carbon isotope discrimination (Δ13Cleaf), and net CO2 assimilation rate (A) by altering stomatal traits and elevating leaf abscisic acid concentration ([ABA]leaf), resulting in lower biomass accumulation. In contrast, biochar amendment of WSB and CSB significantly improved soil water-holding capacity, root water uptake and leaf water status, resulting in lower [ABA]leaf and enhanced stomatal density (SD), stomatal size (SS) and Δ13Cleaf. Notably, PRDI combined with biochar amendment substantially enhanced leaf intrinsic WUE (A/gs) and long-term WUE indicated by lower Δ13Cleaf, thereby increasing plant-scale WUE (WUEplant) by 39–56 % compared to non-biochar-amended under PRDI treatment. Overall, co-application of biochar amendment and deficit irrigation facilitates more efficient and ecologically sustainable alfalfa management in salt-affected soil. Future studies should investigate long-term effects, underlying mechanisms, and large-scale applicability across diverse environmental contexts.